The effects of calcitriol on microalbuminuria in patients with type 2 diabetes mellitus; a double-blind randomized clinical trial - Maryam Askari; Akram Ghadiri-Anari; Asma Jaafarinia; Shadab Kharazmi; Roya Hemayati (Journal of Nephropathology)
Introduction: Diabetes mellitus (DM) is a metabolic disorder appearing as a main public health problem nowadays. Objectives: This study aimed to evaluate the effect of calcitriol on microalbuminuria in patients with type 2 DM (T2DM). Patients and Methods: This double-blind randomized clinical trial was performed on 38 patients with T2DM who had micro- albuminuria. These patients were randomly classified into two groups of treatment and control. The treatment group received calcitriol 0.25 μg daily since the control group received a placebo. Duration of treatment was three months. In baseline, serum creatinine (Cr), fasting blood sugar (FBS), glycated hemoglobin (HbA1c), cholesterol (Chol), triglyceride (TG), low-density lipoprotein (LDL-c), high-density lipoprotein (HDL-c), and micro-albuminuria were measured. Patients were followed up for three months. P<0.05 was set as a significant level. Results: In baseline, two groups did not differ significantly in terms of serum Cr, FBS, HbA1c, Chol, TG, HDL-c, LDL-c, and micro-albuminuria (P> 0.05). After the intervention, there was no significant difference between the two groups regarding the median of serum Cr, FBS, HbA1c, Chol, TG, LDL-c, HDL-c, and microalbuminuria. The median of microalbuminuria in the treatment and control groups was decreased at 46 mg/g and 11 mg/g, respectively. The difference in median of micro-albuminuria was not statically significant between the two groups; however, a significant difference was detected in the treatment group before and after the intervention (P=0.03). Conclusion: Administration of calcitriol could reduce micro-albuminuria after three months. Therefore, the addition of calcitriol to angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) in patients with T2DM and micro- albuminuria may have a beneficial effect on reducing their proteinuria. Trial Registration: The trial protocol was approved by the Iranian Registry of Clinical Trials (identifier: IRCT2016091429812N; https://en.irct.ir/trial/23865, ethical code; IR.SSU.Rec.65415).